Pesticide use in banana and plantain production and risk perception among local actors in Talamanca, Costa Rica - Barraza, Douglas (2011)
The Talamanca County in Costa Rica has large-scale banana and small-scale plantain production, probably causing pesticide exposure in indigenous children. We explored to what extent different community actors are aware of children’s pesticide hazards and how their awareness related to socioeconomical and cultural conditions. Methods comprised eight focus groups with fathers and mothers separately, 27 semi-structured interviews to key actors, and field observations. As a whole, the indigenous plantain farmers and banana plantation workers had some general knowledge of pesticides concerning crop protection, but little on acute health effects, and hardly any on exposure routes and pathways, and chronic effects. People expressed vague ideas about pesticide risks. Inter-community differences were related to pesticide technologies used in banana and plantain production, employment status on a multinational plantation versus smallholder status, and gender. Compared to formalized practices on transnational company plantations, where workers reported to feel protected, pesticide handling by plantain smallholders was not perceived as hazardous and therefore no safety precautions were applied. Large-scale monoculture was perceived as one of the most important problems leading to pesticide risks in Talamanca on banana plantations, and also on neighboring small plantain farms extending into large areas. Plantain farmers have adopted use of highly toxic pesticides following banana production, but in conditions of extreme poverty. Aerial spraying in banana plantations was considered by most social actors a major determinant of exposure for the population living nearby these plantations, including vulnerable children. We observed violations of legally established aerial spraying distances. Economic considerations were most mentioned as the underlying reason for the pesticide use: economic needs to obtain the production quantity and quality, and pressure to use pesticides by other economic agents such as middlemen. Risk perceptions were modulated by factors such as people’s tasks and positions in the production process, gender, and people’s possibilities to define their own social conditions (more fatalistic perceptions among banana workers). The challenge for the future is to combine these insights into improved health risk assessment and management that is culturally adequate for each particular community and agricultural context.